Analisis Kebutuhan Bahan Ajar - Ayu Dien Islamiyati; Bowo Sugiharto; Baskoro Adi Prayitno (Postgraduate, University of Mataram, 2021)
The aim of this study is to analyze the need for teaching materials in the Biology Learning Strategy course that are in accordance with the needs of lecturers and students to support learning in the modern era. The design of this research is exploratory research. The research subjects were ten lecturers in Biology Learning Strategy courses or similar courses from seven universities and 102 biology education students who had gone through Biology Learning Strategies courses from Universities in Surakarta and DIY. Data collection techniques are observation and questionnaires. Analysis of questionnaire data using Rasch modeling. The results of the study indicate that the obstacles faced in learning the Biology Learning Strategy course are the absence of teaching materials that can be used as a guide in the learning process. The results of the questionnaire analysis of lecturers and students are above the logit item value of 0.00 which shows the respondents agree on the importance of the Biology Learning Strategy course and that teaching materials are needed in the form of textbooks. The conclusion of this research is that it is necessary to develop a textbook with the characteristics of Blended Collaboration Problem-Based Learning to support the Biology Learning Strategy course.